Detection of Agents That Alter the Bacterial Cell Surface - Sud, Inder Jit (1975)
Proteus mirabilis is not killed by polymyxin B, normal serum, or sodium deoxycholate. Exposure to polymyxin B renders the cells susceptible to killing by the latter two agents. The data suggest that this synergism is due to polymyxin B-induced surface changes. The results point out an inadequacy of existing methods of screening for antibiotics; they fail to detect agents which, while showing no in vitro effect on growth, may alter a resistant organism so that it becomes more susceptible to other antimicrobials or host defense mechanisms. A method is described which can be used to detect such cell surface-modifying agents.